2016
DOI: 10.1111/evo.12939
|View full text |Cite
|
Sign up to set email alerts
|

Linking intra- and interspecific assortative mating: Consequences for asymmetric sexual isolation

Abstract: Assortative mating is of interest because of its role in speciation and the maintenance of species boundaries. However, we know little about how within-species assortment is related to interspecific sexual isolation. Most previous studies of assortative mating have focused on a single trait in males and females, rather than utilizing multivariate trait information. Here, we investigate how intraspecific assortative mating relates to sexual isolation in two sympatric and congeneric damselfly species (genus Calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 90 publications
(275 reference statements)
0
14
0
Order By: Relevance
“…Also, our previous experimental work has shown that C. virgo males discriminate strongly against C. splendens females (Svensson et al. , ), suggesting that such heterospecific males should not affect C. splendens female survival directly, but only possibly indirectly through these heterospecific males interactions with C. splendens males, which we aimed to investigate in this study. Based on these features of the natural history and ecology of these damselfly species, we therefore feel confident in our assumption that conspecific male density and species composition are the two most important factors that are likely to affect C. splendens female survival, with little or no effect of female–female interactions or heterospecific male–female interactions.…”
Section: Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…Also, our previous experimental work has shown that C. virgo males discriminate strongly against C. splendens females (Svensson et al. , ), suggesting that such heterospecific males should not affect C. splendens female survival directly, but only possibly indirectly through these heterospecific males interactions with C. splendens males, which we aimed to investigate in this study. Based on these features of the natural history and ecology of these damselfly species, we therefore feel confident in our assumption that conspecific male density and species composition are the two most important factors that are likely to affect C. splendens female survival, with little or no effect of female–female interactions or heterospecific male–female interactions.…”
Section: Methodsmentioning
confidence: 92%
“…, , Svensson et al. , , , , ) strongly suggest that interspecific interactions can modify the outcome of sexual conflict through interspecific reproductive interference between males. Our results call for the incorporation of more ecological realism in the study of sexual conflict, particularly how local community composition interspecific interactions could have different fitness consequences for the two sexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations